2018
DOI: 10.1177/0192513x18783494
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Decision Making in Spain: Heterosexual Couples’ Narratives About How They Chose to Have Children

Abstract: This article seeks to expand researchers’ understanding of choice in the reproductive decision-making narratives of heterosexual couples to help explain fertility rates in Spain. The data comprise 32 interviews and two focus groups with heterosexual mothers and fathers. Two broad categories have been identified: couples who chose “when” to have children and couples who chose “whether” to have children. The results show that couples choosing “when” considered having children to be a normal step in the life cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 59 publications
1
18
0
2
Order By: Relevance
“…Doubters were also most worried that parenthood would imply loss of autonomy and freedom. These results can be related to findings from a Spanish study, where couples who discussed 'whether' to have children saw parenthood as a free, individual choice, while couples who talked about 'when' saw parenthood as a normal step in life (Alvarez, 2018). The present results indicate that if one sees procreation as a natural and biological impetus, one might not be that likely to consider the negative aspects of bringing new life to earth, but rather worry about not having found the right partner or consider practical issues (i.e.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Doubters were also most worried that parenthood would imply loss of autonomy and freedom. These results can be related to findings from a Spanish study, where couples who discussed 'whether' to have children saw parenthood as a free, individual choice, while couples who talked about 'when' saw parenthood as a normal step in life (Alvarez, 2018). The present results indicate that if one sees procreation as a natural and biological impetus, one might not be that likely to consider the negative aspects of bringing new life to earth, but rather worry about not having found the right partner or consider practical issues (i.e.…”
Section: Discussionsupporting
confidence: 54%
“…Men who did not want children, on the other hand, mostly worried about the future of the world, practicalities and their skills as parents. Most reasons given against having children have been described before (Agrillo and Nelini, 2008;Alvarez, 2018;Henwood et al, 2011;Park, 2005). As for worry about the future, Overall and Caplan welcome this ethical discussion, claiming that the so-called urge or natural drive to procreate is not, in itself, a justification for action (Overall and Caplan, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Alvarez (2018) categorizes fertility decision-making into “whether” and “when” questions. Her research suggests that the decision to have the first baby requires contemplation and negotiation between partners.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is important to explore fertility intentions, reproductive choices may be a more effective predictor of how effectively the universal two-child policy has been received. However, women’s reproductive choices are rarely explored in research, either in English or in Chinese, with only a few exceptions (Alvarez, 2018; Mao & Luo, 2013). This paper intends to remedy this situation by focusing on the reproductive choices of highly educated employed women in Shanghai.…”
Section: Introductionmentioning
confidence: 99%
“…This study also builds on previous research on reproductive decision-making, which in the context of the USA showed how contingent reproduction was, particularly for gay men, most of whom were found to be ‘situational parents’ (Stacey, 2006). Reproductive contingency was also found to be the case for heterosexual men in the USA, UK, Australia and South Africa (Bartholomaeus and Riggs, 2017, Blell, 2018, Marsiglio, 1991, Morison, 2013), as well as for heterosexual couples in Spain (Alvarez, 2018) – only half of the latter wondered when to have children, whilst the other half wondered whether to actually have children at all. This reproductive contingency could be attributed to different factors that may deter individuals from parenthood: postmodern values of self-fulfilment (Giddens, 1992); pressures on ‘intensive parenting’ (Faircloth and Gurtin, 2017); poor child-care services in the neoliberal context (Briggs, 2017), to which in case of gay men are added increased practical, symbolic and other difficulties to actually achieve parenthood.…”
Section: Introductionmentioning
confidence: 94%